2019
DOI: 10.1186/s12891-019-2500-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-rich plasma in arthroscopic repair for discoid lateral meniscus tears

Abstract: BackgroundTo evaluate the clinical results of arthroscopic repair with or without platelet-rich plasma (PRP) for tears of the discoid lateral meniscus (DLM).MethodsTwenty-nine patients with DLM tears within a stable knee were arthroscopically treated with meniscal suture repair. Of those, 14 were augmented with platelet-rich plasma (PRP), and 15 were performed without PRP augmentation. Patients were evaluated at baseline (the day before surgery) and then 12 and 24 months after the last injection. Evaluation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
87
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(95 citation statements)
references
References 30 publications
2
87
1
Order By: Relevance
“…One study was at high risk of bias for five domains [51], four studies were at high risk of bias for four domains [49,50,52,53], and two studies were at high risk of bias for two domains [47,48]. High risk of performance bias was identified in five studies [49][50][51][52][53] and moderate risk of performance bias was identified in two studies [47,48] (Figure 9C). One study was at high risk of bias for five domains [51], four studies were at high risk of bias for four domains [49,50,52,53], and two studies were at high risk of bias for two domains [47,48].…”
Section: Meniscal Repairmentioning
confidence: 98%
See 4 more Smart Citations
“…One study was at high risk of bias for five domains [51], four studies were at high risk of bias for four domains [49,50,52,53], and two studies were at high risk of bias for two domains [47,48]. High risk of performance bias was identified in five studies [49][50][51][52][53] and moderate risk of performance bias was identified in two studies [47,48] (Figure 9C). One study was at high risk of bias for five domains [51], four studies were at high risk of bias for four domains [49,50,52,53], and two studies were at high risk of bias for two domains [47,48].…”
Section: Meniscal Repairmentioning
confidence: 98%
“…Two RCTs [47,48] and five non-randomized studies [49][50][51][52][53] evaluated the use of PRP in meniscus healing. In five studies, PRP was injected after arthroscopic meniscus repair [47,49,50,52,53], in one study patients underwent open meniscal repair with an adjunct of PRP [51], and in another the authors compared percutaneous meniscal trephination with or without PRP [6].…”
Section: Meniscal Repairmentioning
confidence: 99%
See 3 more Smart Citations